Revitalization of 21st Century Learning: Enhancing Teachers' Digital Literacy and Technology Skills through Canva Design Training - Rahmadona Safitri; Denny Kurniadi (SEAMEO SEAMOLEC, 2024)
The demands of 21st-century education necessitate educators to possess robust digital literacy and pertinent technological competencies. This paper explores initiatives aimed at bolstering educators' digital literacy and technological adeptness through Canva design training utilizing the development study approach. By concentrating on the online graphic design platform during training sessions, educators can hone their abilities in crafting captivating and interactive learning materials. Purposive sampling was utilized in this study, selecting participants based on predefined criteria aligned with the research goals, particularly students enrolled in the Initial Teacher Professional Education Program (PPG Prajabatan) batch 1 for the academic year 2023/2024 across diverse educational fields. Research findings reveal that 90% of the 50 participating educators attested to their capability to generate compelling learning resources catering to the needs of 21st-century learners. Surveys among students further illustrate an 80% increase in interest and engagement in learning subsequent to Canva utilization. Consequently, Canva training substantially elevates the quality of learning materials and student involvement in the educational process. Targeted training equips educators to adeptly address the requisites of 21st-century education, thus facilitating an enhanced learning experience for students. This research contributes to discussions surrounding the professional development of educators in the digital age.